GZD824 overcomes FGFR1‐V561F/M mutant resistance in vitro and in vivo. (10th June 2021) - Jiang, Kaili; Tang, Xia; Guo, Jing; He, Rui; Chan, Shingpan; Song, Xiaojuan; Tu, Zhengchao; Wang, Yuting; Ren, Xiaomei; Ding, Ke; Zhang, Zhang
Abstract: Abnormallyactivated FGFR1 has been validated as a therapeutic target for differentcancers. Although a variety of FGFR inhibitors have shown benefit in manyclinical patients with FGFR1 aberration, FGFR1 mutant resistance such as V561Mmutation, has been reported. To date however, no FGFR inhibitors have beenapproved to treat patients with FGFR mutant resistance. Herein, we report that GZD824, athird generation ABL inhibitor (Phase II, China), overcomes FGFR1‐V561F/M mutant resistance in vitro and in vivo. GZD824potently suppresses FGFR1/2/3 with an IC50 value of 4.14 ± 0.96, 2.77 ± 0.082, and 8.10 ± 0.15 nmol/L. It effectively overcomes FGFR1‐V561F/M and other mutantresistance in Ba/F3 stable cells (IC50 :8.1–55.0 nM), and effectively inhibits the growth of Ba/F3‐FGFR1‐V561F/M mutantxenograft tumors in vivo (TGI=73.4%, 49.8% at20mg/kg, p.o, q2d). GZD824may be considered to be an effective drug to treat patients with FGFR1 abnormalactivation or mutant resistance in clinical trials. Abstract : FGFR1‐V561F/M mutation is resistant to erdafitinib, pemigatinib, BGJ398, and TAS120 but sensitive to GZD824. GZD824 strongly suppresses FGFR1‐3 and effectively overcomes FGFR1‐V561F, V561M, and other mutant resistance in vitro (IC50 :8.1–55.0 nM) and in vivo (TGI=73.4%, 49.8% at 20mg/kg, p.o, q2d). GZD824 as a type II FGFR1 inhibitor overcomes FGFR1‐V561F/M mutant resistance.